Comparison of MEMS switches and PIN diodes for switched dual tuned RF coils. Issue 4 (9th March 2018) - Maunder, Adam; Rao, Madhwesha; Robb, Fraser; Wild, Jim M.
Abstract : Purpose: To evaluate the performance of micro‐electromechanical systems (MEMS) switches against PIN diodes for switching a dual‐tuned RF coil between 19 F and 1 H resonant frequencies for multi‐nuclear lung imaging. Methods: A four‐element fixed‐phase and amplitude transmit–receive RF coil was constructed to provide homogeneous excitation across the lungs, and to serve as a test system for various switching methods. The MR imaging and RF performance of the coil when switched between the 19 F and 1 H frequencies using MEMS switches, PIN diodes and hardwired configurations were compared. Results: The performance of the coil with MEMS or PIN diode switching was comparable in terms of RF measurements, transmit efficiency and image SNR on both 19 F and 1 H nuclei. When the coil was not switched to the resonance frequency of the respective nucleus being imaged, reductions in the transmit efficiency were observed of 32% at the 19 F frequency and 12% at the 1 H frequency. The coil provides transmit field homogeneity of ±12.9% at the 1 H frequency and ±14.4% at the 19 F frequency in phantoms representing the thorax with the air space of the lungs filled with perfluoropropane gas. Conclusion: MEMS and PIN diodes were found to provide comparable performance in on‐state configuration, while MEMS were more robust in off‐state high‐powered operation (>1 kW), providing higher isolation and requiring a lower DC switching voltage than is needed for reverse biasing of PIN diodes. In addition, clear benefits of switching between the 19 F and 1 H resonances were demonstrated, despite the proximity of their Larmor frequencies.